Dynamic voltage restorer (DVR) enhancement in power quality mitigation with an adverse impact of unsymmetrical faults. (April 2022) - Farooqi, Awais; Othman, Muhammad Murtadha; Radzi, Mohd Amran Mohd; Musirin, Ismail; Noor, Siti Zaliha Mohammad; Abidin, Izham Zainal
Abstract: Solar grid systems are widely used especially in remote locations where electricity accessibility from the grid is limited. The major issue frequently encountered in microgrid-connected photovoltaic (PV) systems are voltage overshoots, transient response and steady state errors causing instability of microgrid during unsymmetrical temporary faults in the distribution network and damages the sensitive loads. PV-grid solely depends on solar hours per day and is not reliable at location with variable weather conditions. Therefore, the generated power per day is reduced as per daily demand and would create power quality issues in a distribution line. Additionally, the PV-grid system exposed to weather experiences unsymmetrical faults due to severe weather conditions that affects the reliability of the grid and electricity supplies. This study presents a technique to enhance the stability of microgrid by using dynamic voltage restorer in a three-phase grid connected system to mitigate power quality issues arising from PV-grid side in a harsh weather condition. The most significant extreme weather conditions such as thunderstorms and high winds are potential causes affecting the instability of transmission network by generating faults such as double line-to-ground, single line-to-ground, lightning strike or impulse transients, and power outage in a distribution line. The proposed technique enhances the transient stability of microgrid and provides symmetrical operating conditions for the load. The control mechanism extracts the fault signal and stabilize the error signal. In the proposed configuration, hysteresis-band PWM generator drives the inverter with the PV based battery storage system connected at DC-Link. The simulation results are verified by using IEEE519 standards limits in four case studies to mitigate power quality issues arising due to severe weather conditions by injecting compensating voltage to protect load and act as microgrid in case of power outage.